LDOC1 regulates Wnt5a expression and osteosarcoma cell metastasis and is correlated with the survival of osteosarcoma patients - Bi-Cheng Yong; Jin-Chang Lu; Xian-Biao Xie; Qiao Su; Ping-Xian Tan; Qing-Lian Tang; Jing Wang; Gang Huang; Ju Han; Hong-Wen Xu; Jing-Nan Shen (Tumor Biology)
Osteosarcomas are common bone malignancies in children and adolescents. LDOC1 (leucine zipper, down-regulated in cancer 1), a tumor suppressor, is down-regulated in many cancers. In this study, we investigated the role of LDOC1 in tumor metastasis and its prognostic significance in osteosarcomas. We established osteosarcoma cells stably expressing LDOC1, driven by an HIV-based lentiviral system. We investigated the impact of LDOC1 on migration and invasion abilities in these cells using a transwell assay. LDOC1-associated changes in expression of metastasis-promoting genes were analyzed with a quantitative real-time polymerase chain reaction primer array. A xenograft tumor model (n = 7 mice/group) was used to assess the effect of LDOC1 on osteosarcoma metastasis in vivo. The overall survival and disease-free survival of osteosarcoma patients (n = 74) were analyzed retrospectively based on immunohistochemical analysis of LDOC1 levels in tumors and Kaplan–Meier analysis. LDOC1-expressing osteosarcoma cells displayed decreased migration and invasion in vitro. The quantitative real-time polymerase chain reaction primer array data showed that increased LDOC1 expression up-regulated many metastasis-suppressor genes. In the xenograft model, micro-computed tomography imaging data indicated that increased LDOC1 expression is associated with weaker lung metastasis ability. The Wnt5a signaling pathway promotes osteosarcoma metastasis; LDOC1 expression decreased Wnt5a levels in osteosarcoma cells. Kaplan–Meier analysis showed that higher LDOC1 expression was associated with improved osteosarcoma patient overall survival and disease free survival (p = 0.022). Our data show that LDOC1 is a tumor suppressor in osteosarcoma, and that it regulates metastasis of osteosarcoma cells. Furthermore, LDOC1 might be a valuable prognostic marker in osteosarcomas.